PRIMATA BESAR DI JAWA: SPESIMEN BARU GIGANTOPITHECUS DARI SEMEDO - Sofwan Noerwidi (Berkala Arkeologi, 2016)
In 2014 there was found two "enigmatic" specimens of mandible, which named as Semedo 3417 and 3418. Both mandibles are morphologically similar but twice bigger than common primate’s jaw. In this research, we use morphology and morphometric analysis to determine the species identity and taxonomic position of those specimens. For comparison study we use some samples from Homo erectus (Java and China), Gigantopithecus (blacki and bilaspurensis), Australopithecines (robust and gracile). Based on morphology and morphometric characters on the mandible and teeth, it is concluded that Semedo specimen tends to be close to Gigantopithecus blacki. The discoveries of Gigantopithecus fossil in Java has implication on some research problem, especially regarding the adaptation pattern of this species which known only found at high latitudes environment. Furthermore this discovery has reinforced the perspective that tropical environment has a very high biodiversity, particularly on primate fossils.